Improvement of Ferroelectricity and Fatigue Property of Thicker HfxZr1−XO2/ZrO2 Bi-layer. (8th September 2020) - Onaya, Takashi; Nabatame, Toshihide; Inoue, Mari; Jung, Yong Chan; Hernandez-Arriaga, Heber; Mohan, Jaidah; Kim, Harrison Sejoon; Sawamoto, Naomi; Nagata, Takahiro; Kim, Jiyoung; Ogura, Atsushi
Abstract : We studied the ferroelectricity of the metal–ferroelectric–metal capacitors with a Hfx Zr1−x O2 (10 nm) (HZO) single layer, and Hfx Zr1−x O2 (10 nm)/ZrO2 (10 nm) (HZO/ZO) and Hfx Zr1−x O2 (10 nm)/HfO2 (10 nm) (HZO/HO) bi-layers. HZO/ZO and HZO exhibited high remanent polarization (2 P r = P r + − P r − ) of 13 and 12 µC/cm 2, respectively, compared to HZO/HO (0.5 µC/cm 2 ) after 10 4 wake-up cycles. This is due to the difference of the amount of ferroelectric orthorhombic phase. We found that the breakdown voltage of HZO/ZO was approximately 1.5 times higher than that of HZO while maintaining a high 2 P r value. Moreover, HZO/ZO kept 1.4 times higher 2 P r value than HZO after 10 6 switching cycles because the phase transformation from anti-ferroelectric to ferroelectric phase of ZrO2 layer in HZO/ZO could occur during field cycling. Therefore, HZO/ZO bi-layer using the combination of HZO and ZrO2 layers is one of the promising ferroelectric layer for future ferroelectric devices application.